The Use of Hair Cortisol as a Biomarker of Chronic Stress in Patients with a recent Acute Myocardial Infarction - Mabotha, Ernest Magee (Division of Dermatology, 2022)
Background Acute Myocardial infarction (MI) or heart attack is a leading cause of death worldwide. Since an MI is a stressful life event, plasma cortisol levels are expected to increase significantly from the baseline. Cortisol and dehydroepiandrosterone (DHEA) as products of the hypothalamicpituitary-adrenal (HPA)-axis have been used to diagnose endocrine disorders in serum, urine and saliva. However, these body fluids reflect short-term assessments. Hair is a promising alternative and offers several advantages over serum e.g. hair collection is painless, provides a longer detection window (days to months depending on length) and is easy to store. Recent studies confirm good correlation between hair cortisol levels and validated stress questionnaires (i.e., hair cortisol is a biomarker of stress). It is unclear whether stress is a result or cause of acute MI (i.e., chicken or egg). The primary aim of this study was to determine whether hair cortisol is higher in patients with acute MI versus healthy controls and whether the higher levels pre-date acute MI (i.e. is hair cortisol a reliable biomarker of chronic stress that predates acute MI). Methods This pilot study aimed to include 25 age-matched controls and acute MI cases, both 25 STelevation myocardial infarctions (STEMIs) and 25 non-ST-elevation myocardial infarctions (NSTEMIs). Complete versus partial coronary artery occlusion is associated with STEMIs and NSTEMIs respectively. Cortisol levels were measured in 3 cm segments of hair representing 9-12 months of growth (which would be before the heart attack in acute MI cases). The proximal 3 cm closest to the scalp, is estimated to represent 3 months before heart attack. The samples were prepared and analyzed for cortisol concentrations using an enzyme-linked immunoassay kit. In addition, at least three strands of hair from each participant were mounted on a glass slide and subjected to Fourier-Transform Infrared (FTIR) spectroscopy. For cortisol concentrations two-sample Wilcoxon rank-sum (Mann-Whitney) was used for within an individual comparisons and Kruskal-Wallis test was used for within group comparisons (P<0.05 considered significant) For FTIR data Principal Component Analysis (PCA), Orthogonal Projections to Latent Structures Discriminant Analysis (OPLS-DA) and Partial Least Squares (PLS) models were used to compare groups. Results Of the intended sample size of 75, 64 participants (48 acute MI cases and 16 healthy controls) were recruited. The total hair cortisol concentration was significantly higher in acute MI cases than controls [median 23.66 (3.73-209.18) vs. 3.32 (0.37-11.24) pg/mg], (p<0.001), and higher in the hair of STEMI versus NSTEMI cases[35.18 (8.15-209.180 vs. 17.24 (3.73-148.22) pg/mg], (p< 0.01). Further, cortisol levels were similar in proximal versus distal hair segments (within an individual) of STEMIs (p< 0.05) but significantly different in those of NSTEMIs [29.64 (5.87- 148.42) vs 9.94 (5.15-32.95)], (p=0.002). In view of the fact that all 16 controls included were female, the analysis was repeated to include only female study participants[16 controls and 27 cases (10 STEMIs and 17 NSTEMIs)]. The total hair cortisol concentration was also significantly higher in female acute MI cases than controls [median 21.59 (3.73-209.18) vs. 3.32 (0.37-11.24)], (p< 0.001), as well as higher in the hair of STEMI vs. NSTEMI cases [median 37.21 (8.15-209.18) vs. 14.11 (3.73- 148.22pg/mg], (p< 0.05). Further, cortisol levels were similar in proximal versus distal hair segments of STEMIs (p< 0.05) but significantly different in those of NSTEMIs [median 15.26 (5.91-100.41) vs. 9.94 (3.73-37.57)], (p< 0.01). Controls had the lowest cortisol levels and there was no significant difference between proximal and distal hair within the individuals [median 3.18(1.43-7.09) vs. 2.30 (0.68-4.62) pg/mg], (p> 0.05). For FTIR data, OPLS-DA showed a separation between acute MI cases and controls, as well as a separation between STEMIs and NSTEMIs. Further, there was also good correlation between total cortisol concentrations and FTIR spectral data (correlation coefficient = 0.85). Study limitations Although not all intended participants were recruited during the study period, repeating the analysis for only female participants did not alter the findings. Discussion and Conclusions Hair cortisol levels were higher in acute MI cases than controls and significantly higher in STEMIs versus NSTEMIs. Further, FTIR data separated acute MI cases from controls and correlated with cortisol concentrations. Patients with Cushing Disease (CD) are reported to have a higher prevalence of thromboembolic events compared to Cushing Syndrome from adrenal sources, this is thought to be a result of high cortisol levels associated with CD. In this study, STEMIs had the highest cortisol levels which not only predated the acute MI but were unchanged in hair segments correlating with the preceding 9 months (i.e., were chronically consistently high). Interestingly, high cortisol levels also predated the acute MI but more than doubled in the proximal 3 cm hair segments (correlating with 3 months) before the heart attack in NSTEMIs. This study suggests that based on hair cortisol concentrations as a biomarker, chronic constantly high stress predates STEMIs. Although also high in NSTEMIs it is lower than in STEMIs and more than doubles before the onset of an acute MI. The effects of chronic very high cortisol levels on the thromboembolic pathway may be to cause complete (versus partial) coronary artery occlusion in STEMIs. These results require validation in larger studies.